Pembuatan Komposit Poly Lactid Acid – Bentonit untuk Plastik Biodegradable - Salsabila, Syifa; Ridwan, Ridwan; Sariadi, Sariadi (Politeknik Negeri Lhokseumawe, 2024)
Plastic is one of the most important materials in human daily activities because of its versatility. Plastic usually comes from petroleum, so it can't be decomposed. This study aims to determine the effect of the ratio and temperature of mixing poly lactid acid and bentonite on the quality of biodegradable plastic products. With variations in the composition of PLA: Bentonite 17: 3 ; 15: 5; 13 : 7 ; and 11 : 9g and temperature variation when mixing PLA and bentonite 180℃, 190℃, 200℃, 210℃. The synthesized composites were tested for their mechanical strength to determine material characteristics and morphological observations. The results showed that addition of bentonite filler affects the mechanical properties and thermal properties of the material.. The highest tensile strength value was produced by the material with a variation of PLA and bentonite 13 : 7g at a temperature of 200℃ which was 15.29 MPa and the lowest tensile strength value was produced by a material with a variation of PLA and bentonite at a temperature of 190℃ of 1.89 MPa. The morphological tests showed that the surface structure of the 13g PLA and 7g bentonite samples during processing showed that the surface structure of poly lactic acid (PLA) was widely dispersed due to electromagnetic rays. In the Thermo Gravimetric Analyzer test, samples with modified PLA-bentonite with a PLA-bentonite degradation temperature for samples of 17:3 are 320 ℃ - 480 ℃. The degradation temperature of PLA-Bentonite for the 13:7 sample is 420℃ - 520℃.